PERKEMBANGAN LEMBAGA KEUANGAN SYARIAH DAN KONDISI MAKRO EKONOMI DI INDONESIA - Nunung Nurjanah (ITB AAS INDONESIA Surakarta, 2023)
The growth of Islamic banking in Indonesia since its inception until now has continued to increase, both in terms of performance and its contribution to national macroeconomic growth. This paper is structured to determine the contribution of Islamic Banking to the Indonesian economy at a macro level, particularly in the 2018-2022 period (July). The data used in this study is secondary data, namely Time Series data, which consists of Macroeconomic Variables and Islamic Banking SME Financing Growth. The data used is the total financing of SMEs by Islamic banks, the BI Rate or Bank Indonesia interest rate certificates (SBI) which reflect interest rates, and GDP (Gross Domestic Product). Data obtained from Bank Indonesia and the Financial Services Authority (OJK). This analysis is also supported by literature studies from various journals, articles and other related literature. The performance of Islamic banking in 2018-2022 is in the healthy category. The average ROA is 1.6 percent, CAR is 22.32 percent, FDR is 75.39 percent, BOPO is 84.28 percent, NPF is 2.97 percent, and DPK is Rp. 323,418 billion with the highest value of Rp. 382,232 billion in July 2022 and the lowest is Rp. 257.606 billion in 2018.